2018
DOI: 10.3389/fcimb.2018.00281
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in the Abundance and Co-occurrence of Akkermansia muciniphila and Faecalibacterium prausnitzii in the Colonic Mucosa of Inflammatory Bowel Disease Subjects

Abstract: Akkermansia muciniphila and Faecalibacterium prausnitzii, cohabitants in the intestinal mucosa, are considered members of a healthy microbiota and reduction of both species occurs in several intestinal disorders, including inflammatory bowel disease. Little is known however about a possible link between the reduction in quantity of these species, and in which circumstances this may occur. This study aims to determine the abundances and co-occurrence of the two species in order to elucidate conditions that may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
99
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(114 citation statements)
references
References 76 publications
13
99
1
1
Order By: Relevance
“…In addition, analysis of the predicted taxonomic profiles at phylum level revealed that the average abundance of three of the five phyla that are present in the canine core gut microbiota appeared to be altered by diet. Notably, in humans, Faecalibacterium, and in particular Faecalibacterium prausnitzii, is associated with a healthy microbiota (Lopez-Siles et al, 2018). 2; Supporting Information Table S3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, analysis of the predicted taxonomic profiles at phylum level revealed that the average abundance of three of the five phyla that are present in the canine core gut microbiota appeared to be altered by diet. Notably, in humans, Faecalibacterium, and in particular Faecalibacterium prausnitzii, is associated with a healthy microbiota (Lopez-Siles et al, 2018). 2; Supporting Information Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, dogs fed with commercial pet foods, which are typically enriched in fibres and carbohydrates, are associated with a higher abundance of these saccharolytic species, as compared with dogs of the BARF group whose diet was based on a high abundance of animal proteins and fats. Notably, in humans, Faecalibacterium, and in particular Faecalibacterium prausnitzii, is associated with a healthy microbiota (Lopez-Siles et al, 2018). Indeed, as a butyrogenic bacterium, this commensal species has been reported to possess antiinflammatory features and to positively influence the gut physiology (Sokol et al, 2008).…”
Section: Role Of Diet As Modulator Of the Canine Core Gut Microbiotamentioning
confidence: 99%
“…For example, the mucolytic enzymes induced by A. muciniphila increased upon the presence of a butyrogenic gut commensal, Anaerostipes caccae (Chia et al, 2018). Furthermore, the monosaccharides supported by A. muciniphila promoted the proliferation of Faecalibacterium prausnitzii, which converted acetate and lactate into butyrate (Lopez-Siles et al, 2018). It has been shown that A. muciniphila and F. prausnitzii, co-occurring in the mucosa, had a syntrophic relationship with each other and that both species were reduced in inflammatory bowel disease (Lopez-Siles et al, 2018).…”
Section: Interaction Of Akkermansia Muciniphila With the Gut Ecosystementioning
confidence: 99%
“…Furthermore, the monosaccharides supported by A. muciniphila promoted the proliferation of Faecalibacterium prausnitzii, which converted acetate and lactate into butyrate (Lopez-Siles et al, 2018). It has been shown that A. muciniphila and F. prausnitzii, co-occurring in the mucosa, had a syntrophic relationship with each other and that both species were reduced in inflammatory bowel disease (Lopez-Siles et al, 2018). The metabolites were induced by A. muciniphila, even though not completely, and thus created metabolic cross-feeding interactions in the gut ecosystem.…”
Section: Interaction Of Akkermansia Muciniphila With the Gut Ecosystementioning
confidence: 99%
“…Akkermansia muciniphila is a mucin degrading, gram-negative intestinal bacterium widely present in the human population, typically at 1 to 4% relative abundance [1, 2]. A number of studies in humans [35] and rodents [68] have found positive associations between its abundance and intestinal health, suggesting that Akkermansia may be a beneficial member of the gut microbiome and could be used as a biomarker of a healthy gut [911]. However, despite a diversity of phylotypes being reported by previous sequence-based studies, A. muciniphila Muc T (ATCC BAA-835) represents the sole described species of the Verrucomicrobia phylum associated with humans [2, 12, 13].…”
Section: Introductionmentioning
confidence: 99%